In vial thin-film solid-phase microextraction using silver nanoparticles as coating for the determination of phenols in waters - Alejandro Rodríguez-González; Ana I. Jiménez-Abizanda; Verónica Pino; Adrián Gutiérrez-Serpa (Journal of Chromatography Open)
A novel thin-film solid-phase microextraction (TF-SPME) device based on glass vials internally coated with silver nanoparticles (AgNPs) was developed for the first time, and used for determining five phenols in wastewater, bottled water, and irrigation water samples by high-performance liquid chromatography coupled to a photodiode array detector (HPLC-PDA). Different AgNPs were synthesized varying the ratio of metallic salt versus the reduction agent, and the pH of the synthesis. The preparation of the TF-SPME glass vial device was optimized in terms of the type of AgNPs used and the number of layers of AgNPs. Besides, the TF-SPME procedure was also optimized. The TF-SPME method was very simple, only requiring the addition of 18 mL of water and 5 min of agitation, followed by the disposal of the water and addition of the 750 µL as desorption solvent, and direct HPLC-PDA injection. The entire method showed adequate analytical performance, with limits of detection ranging from 3 to 8 μg·L-1, and intra-day and inter-day precision (as RSD), both evaluated with different vials and therefore showing inter-batch precision, with values between 8.70 and 16.4 %, and 6.0 and 19.7 %, respectively. The TF-SPME-HPLC-PDA procedure was compared with previous methods for the determination of phenols, both in terms of analytical performance and greenness assessments applying different metrics, showing clear advantages.